3D Modeling and Volume Estimation of Riverbed Layers Based on Sub Bottom Profiler Measurement Data - Nurkhalis Rahili Rahili; Bambang Kun Cahyono (Jurnal Geospasial Indonesia, 2019)
The river is one of the transportation routes for human beings, as well as the pipelines for oil and gas distribution, or as power cable lines and communications networks. In order to not disturb the pipe or cable due to the activity of the ship through the river, it is necessary to study the sediment from the river. This study aims to determine the type of sediment, the thickness of the sediment, the depth of sediment, and volume of the sediment itself. It can be done with acoustic measurements.The measurement of the acoustic survey in this activity uses a sub bottom profiler Strata Box HD type Chirp. By using this tool, it can obtain sediment layer up to a certain depth. The result of the measurement will be interpreted to obtain the travel time of the acoustic wave as it reflected on the sediment layer. The travel time than processed and corrected with the tidal measurement data which made over 14 days to obtain the actual depth value from the result with the sub bottom profiler. The depth data then were quality tested based on reference IHO SP-44 2008 at order 1a.This activity produces a 3D model of river layer, depth profile and sediment layer volume estimation. The result of the quality tested obtained corrected depth data has met the established standards of order 1a IHO SP-44 2008. Using a 95% confidence level, the test results in the first layer is 0.271 m with an error tolerance at 0.510 m. For the second layer has a data quality test results 0.491 m with a tolerance at 0.521 m. The result of depth profile is a long section and cross section. The long section indicates that in the deflection of the river area there is a steep decline compared to the area before and after the river deflection. In addition, the river deflection area has a thinner sedimentary layer. The volume estimation of sediment layers obtained in the area of the activity is 4932752.739 m3.